Post-War Political Changes, Constitutional Developments Towards Independence And Changing Conceptions Of Judicial Review In Malaysia - Yusoff, Mohd Ariff (Journal of Malaysian and Comparative Law, 2018)
Post-War Political Changes, Constitutional Developments Towards Independence And Changing Conceptions Of Judicial Review In Malaysia – Mohd. Ariff Yusoff